Rhodotron and rotating target: A solution towards micro-spot for high energy and high dose rate bremsstrahlung sources. (November 2022) - He, Xiaozhong; Yang, Liu; Liao, Shuqing; Tang, Ruo; Peng, Yufei; Wang, Yi; Yang, Guojun; Wei, Tao; Yang, Xinglin; Jiang, Xiaoguo; Long, Jidong; Zhang, Huang; et al.
Abstract: High energy over MeV bremsstrahlung sources that employ normal conducting radio frequency linear accelerators have expanding applications in industrial computerized tomography (CT) for non-destructive inspection and evaluation. The X-ray spot size that mainly affects the imaging quality is yet limited by the electron beam width in the high resolution CT systems. In a short exposure time, high beam power is required to generate sufficient photons to improve the signal to noise ratio of imaging. However, with ∼kW level of average beam power these linear accelerators usually have a beam spot size over 1 mm since the temperature rising due to the beam energy deposition in the target should be far below its melting point. We propose a concept of using a Rhodotron-based accelerator to provide high power electron beams in a long duration pulse and a rotating target to mitigate the overheating issue, such that the gap between micro-spot and high dose rate can be bridged in the high energy bremsstrahlung sources. This article presents an in-depth simulation work to discuss and evaluate this scheme of X-ray source. The simulations of beam dynamics in the accelerator and bremsstrahlung process in the target predict the generated X-rays with a spot size as small as 68 μm at full-width half-maximum and a dose rate as high as 4700 cGy/min from a 9 MeV electron beam interacting with a 1 mm thickness tantalum target. Further thermal analysis in the rotating target indicates a significant improvement of beam power handling in comparison with the conventional stationary one. Highlights: Using a 9 MeV Rhodotron is proposed to bridge the gap between micro-spot and high dose rate in the high energy bremsstrahlung sources. This scheme allows using a rotating target to migrate the overheating issue in the target. In-depth simulations suggest X-ray spot size 68 μm at FWHM and dose rate 4700 cGy/min with 1 kW power of incident electron beams. Thermal analysis indicates significant improvement of beam power handling in the target.